PENGGUNAAN BAHASA ISYARAT INDONESIA PADA ORANG TULI DALAM BUDAYA MINANGKABAU - Almos, Rona; Hidayat, Herry N (Jurnal Elektronik WACANA ETNIK, 2021)
The use of Indonesian Sign Language by The Deaf in Minangkabau, particularly in West Sumatra, has become a significant topic to discuss within the context of culture and communication. Sign language serves as an effective communication tool for deaf individuals, enabling them to interact and participate in society in the same way as others. However, there is a significant disparity between the number of deaf individuals and the number of sign language interpreters in West Sumatra, indicating the need for further efforts to promote and support the use of sign language. This research explores how sign language adapts and integrates into Minangkabau culture and its impact on the values, norms, and behaviors within that culture. The research findings indicate that sign language plays a crucial role in the identity of deaf individuals and their integration into society. Furthermore, the study highlights the importance of developing local and national sign language as a crucial step to ensure that deaf individuals have equal access to communication and participation in society. This research emphasizes the importance of understanding and valuing the human rights of deaf individuals, including the right to use sign language, as part of efforts to create an inclusive and fair society.